2021
DOI: 10.1002/adma.202106469
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Aqueous Zinc Batteries Based on Organic/Organic Cathodes Integrating Multiredox Centers

Abstract: V vs the standard hydrogen electrode), ultrahigh theory capacity (820 mAh g −1 ), low cost, fast kinetics, and superior reliability, aqueous zinc-ion batteries (ZIBs) have attracted extensive attention among various rechargeable batteries. [5][6][7][8] However, the energy density and output power density of state-of-the-art ZIBs are mainly limited by the unsatisfactory cathode materials, especially under the commercial mass loading (> 10 mg cm −2 ). [9,10] Considerable research efforts have been put into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 54 publications
(103 reference statements)
0
66
0
Order By: Relevance
“…Figure 3 e displayed the ex-situ O 1 s spectra of the N-OPCNF electrode. During the discharge, the ratio of the characteristic peaks corresponding to the carbonyl group (531.3 eV) decreased continuously, and a new peak at 532.1 eV corresponding to the C–O–Zn bond was detected [ 15 , 49 ]. During the charging process, a reversible increase in the ratio of carbonyl groups was observed, accompanied by the gradual disappearance of the C–O–Zn peak, which indicated that a reversible pseudocapacitance reaction occurred between the Zn 2+ and the carbonyl groups on the surface of the carbon nanofibers [ 41 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 e displayed the ex-situ O 1 s spectra of the N-OPCNF electrode. During the discharge, the ratio of the characteristic peaks corresponding to the carbonyl group (531.3 eV) decreased continuously, and a new peak at 532.1 eV corresponding to the C–O–Zn bond was detected [ 15 , 49 ]. During the charging process, a reversible increase in the ratio of carbonyl groups was observed, accompanied by the gradual disappearance of the C–O–Zn peak, which indicated that a reversible pseudocapacitance reaction occurred between the Zn 2+ and the carbonyl groups on the surface of the carbon nanofibers [ 41 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…[19] Furthermore, the hierarchical configuration of poly(1,5-naphthalenediamine,1 ,5-NAPD) and poly(para-aminophenol, pAP) on nanoporous carbon can facilitate the complete activation of the coordination centers (C=Oand C=N) for Zn 2+ . [20] On the other hand, despite the high theoretical capacity of small organic compounds such as benzoquinone (BQ), their electrochemical stability is poor due to the lack of sufficient covalent structure.T herefore,s imply pursuing high capacity in coordination-type organic compounds may be counterproductive.T he aim is to achieve ag ood balance between structure (carbon skeleton and active groups) and electrochemical performance (cycling stability and capacity).…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al 173 attempted to introduce multiple redox centres into organic composite materials to solve the problem of low capacity due to over-reliance on cations reacting only with a single functional group in zinc batteries. They first electrodeposited poly(1,5-naphthalenediamine, 1,5-NAPD) in situ on nanoporous carbon as the stable intermediate layer and then daubed poly( para -aminophenol, pAP) skin on top of 1,5-NAPD as an external conducting layer.…”
Section: Applications Of Crps In Different Batteriesmentioning
confidence: 99%